Reading as a component of the way of life: a printed book, and/or an electronic text - T. B. Markova (Библиосфера)
The comparative analysis of a traditional book and an electronic text is given, identified are important characteristics of a printed and a e-book. The dynamics of the reading development of as a component of the way of life for different generations in the modern Russian society is shown.